Expanding the phenotype of PIGS‐associated early onset epileptic developmental encephalopathy. (7th January 2021) - Efthymiou, Stephanie; Dutra‐Clarke, Marina; Maroofian, Reza; Kaiyrzhanov, Rauan; Scala, Marcello; Reza Alvi, Javeria; Sultan, Tipu; Christoforou, Marilena; Tuyet Mai Nguyen, Thi; Mankad, Kshitij; Vona, Barbara; Rad, Aboulfazl; et al.
Abstract: The phosphatidylinositol glycan anchor biosynthesis class S protein ( PIGS) gene has recently been implicated in a novel congenital disorder of glycosylation resulting in autosomal recessive inherited glycosylphosphatidylinositol‐anchored protein (GPI‐AP) deficiency. Previous studies described seven patients with biallelic variants in the PIGS gene, of whom two presented with fetal akinesia and five with global developmental delay and epileptic developmental encephalopathy. We present the molecular and clinical characteristics of six additional individuals from five families with unreported variants in PIGS . All individuals presented with hypotonia, severe global developmental delay, microcephaly, intractable early infantile epilepsy, and structural brain abnormalities. Additional findings include vision impairment, hearing loss, renal malformation, and hypotonic facial appearances with minor dysmorphic features but without a distinctive facial gestalt. Four individuals died due to neurologic complications. GPI anchoring studies performed on one individual revealed a significant decrease in GPI‐APs. We confirm that biallelic variants in PIGS cause vitamin pyridoxine‐responsive epilepsy due to inherited GPI deficiency and expand the genotype and phenotype of PIGS ‐related disorder. Further delineation of the molecular spectrum of PIGS ‐related disorders would improve management, help develop treatments, and encourage the expansion of diagnostic genetic testing to include this gene as a potential cause of neurodevelopmental disorders and epilepsy.